TRA DANIMARCA, SVIZZERA E ITALIA. LA VISIONE POLIPROSPETTICA DEL VIAGGIO NELLA PRIMA FASE DELLA PRODUZIONE MIGRANTE DI ELVIRA DONES - Karp, Karol (Studia Europaea Gnesnensia, 2018)
The article aims to analyze the problem of travel writing, define its typology and discuss the outcomes of travelling as they are unfolded in the first phase of Elvira Dones’s migrant writings. It addressess three phenomena: travelling to Denmark, travelling to Sweden and travelling to Italy, outlining the influence of space on the lives of the characters. The theoretical foundation derives from research by T.W. Adorno, G. Bataille, E. Grosz, S. Hurn, I. Illich, M. Marzano, S. Mezzadra, M. Midgley, M.C. Nussbaum and P. Ricoeur.